Генеалогическая и типологическая особенность тюркских языков. - Esenalyeva., Zh. (Journal of Oriental Studies, 2016)
The article is dedicated the cognitive processes of Turkic written monuments. The relevance of this work is duo to the fact that for the first time the study was carried out on the above-mentioned processes, comparative historical cut in the terms of diachronic and synchronic.